Comparative genomics and transcriptomics of Chrysolophus provide insights into the evolution of complex plumage coloration. Issue 10 (6th September 2018) - Gao, Guangqi; Xu, Meng; Bai, Chunling; Yang, Yulan; Li, Guangpeng; Xu, Junyang; Wei, Zhuying; Min, Jiumeng; Su, Guanghua; Zhou, Xianqiang; Guo, Jun; Hao, Yu; et al.
Abstract: Background: As one of the most recognizable characteristics in birds, plumage color has a high impact on understanding the evolution and mechanisms of coloration. Feather and skin are ideal tissues to explore the genomics and complexity of color patterns in vertebrates. Two species of the genus Chrysolophus, golden pheasant ( Chrysolophus pictus ) and Lady Amherst's pheasant ( Chrysolophus amherstiae ), exhibit brilliant colors in their plumage, but with extreme phenotypic differences, making these two species great models to investigate plumage coloration mechanisms in birds. Results: We sequenced and assembled a genome of golden pheasant with high coverage and annotated 15, 552 protein-coding genes. The genome of Lady Amherst's pheasant is sequenced with low coverage. Based on the feather pigment identification, a series of genomic and transcriptomic comparisons were conducted to investigate the complex features of plumage coloration. By identifying the lineage-specific sequence variations in Chrysolophus and golden pheasant against different backgrounds, we found that four melanogenesis biosynthesis genes and some lipid-related genes might be candidate genomic factors for the evolution of melanin and carotenoid pigmentation, respectively. In addition, a study among 47 birds showed some candidate genes related to carotenoid coloration in a broad range of birds. The transcriptome data further reveal important regulators of the two colorations, particularly one splicing transcript of the microphthalmia-associated transcription factor gene for pheomelanin synthesis. Conclusions: Analysis of the golden pheasant and its sister pheasant genomes, as well as comparison with other avian genomes, are helpful to reveal the underlying regulation of their plumage coloration. The present study provides important genomic information and insights for further studies of avian plumage evolution and diversity.